MODERN MAN AS A SPIRIT-LESS CREATURE WITH REGARD TO THE POEM THE HOLLOW MAN BY T.S ELIOT - Imranullah; Thaterra Achakzai (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study aims to explore the hollow nature of modern man with specific reference to T.S Eliot’s poem “The Hollow Man”. The paper has deeply explored the hollowness and spirit-less creature of modern man which the author has highlighted in the poem. The current study has explored the poem "The Hollow Men" which is a bleak and haunting exploration of the disillusionment and spiritual emptiness of the post-World War I era. It reflects Eliot's sense of the moral and cultural crisis of his time and his belief that humanity had lost its way. The poem's complex imagery and fragmented structure invite multiple interpretations, but at its core, it conveys a sense of despair and the search for meaning in a world that seems devoid of it. The study is qualitative in nature, based on the textual analysis of the poem. Through textual analysis and thematic analysis, the study will deepen one's understanding of poetic techniques and literary modernism and will also enrich the human understanding of emptiness, alienation, spiritual crisis, spiritual desolation, existential crisis, and hollowness of modern human beings.